2014
DOI: 10.1002/syn.21774
|View full text |Cite
|
Sign up to set email alerts
|

Functional adaptation of presynaptic chemokine receptors in EAE mouse central nervous system

Abstract: In cortical synaptosomes of Experimental Autoimmune Encephalomyelitis (EAE) mice at the early stage of disease (13 days post immunization, d.p.i.), the Regulated upon Activation Normal T cell Expressed and Secreted (RANTES, CCL5)-mediated control of [3H]D-aspartate ([3H]D-ASP) exocytosis elicited by a mild depolarizing stimulus (12 mM KCl) shifted from inhibition to facilitation. By using selective antagonists for the chemokine receptor (CCR) 1, 3, and 5 subtypes, we found that the pharmacological profile of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The KCl‐evoked [ 3 H]‐ d ‐Asp overflow was dramatically reduced from synaptosomes isolated from the cortex of EAE mice at the early stage of disease (13 d.p.i. ), but it was significantly increased from nerve terminals isolated from the spinal cord of EAE mice at the acute stage of disease (21 d.p.i., Table , but see Di Prisco et al , ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The KCl‐evoked [ 3 H]‐ d ‐Asp overflow was dramatically reduced from synaptosomes isolated from the cortex of EAE mice at the early stage of disease (13 d.p.i. ), but it was significantly increased from nerve terminals isolated from the spinal cord of EAE mice at the acute stage of disease (21 d.p.i., Table , but see Di Prisco et al , ).…”
Section: Resultsmentioning
confidence: 97%
“…Depending on the animal model used and the brain region under study, opposite modifications of glutamate release capability were observed in selected CNS regions, indicating that glutamate impairment in MS is a complex event. In particular, increased glutamate release was detected in the spinal cord of EAE rats (Sulkowski et al , ) and mice (Di Prisco et al ., ) as well as in striatal and spinal cord nerve terminals of EAE mice (Centonze et al , ; Marte et al , ; Di Prisco et al , ), while reduced glutamate release was observed in cortical nerve endings of both mice and rats suffering from EAE (Vilcaes et al , ; Di Prisco et al , ). As for glutamate receptors, previous studies have shown that both mGlu 1/5 and mGlu 4 receptors are suitable targets of drugs for ameliorating MS symptoms (Besong et al , ; Fazio et al , , Fallarino et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, depending on the animal model used and the brain region under study, opposite modifications of glutamate release efficiency were observed, consistent with the view that, in demyelinating disorders, impaired glutamate transmission at active synapses is a complex event. Increased glutamate release was detected in the spinal cord of EAE rats ( 123 , 124 ) as well as in striatal and spinal cord nerve terminals of EAE mice ( 72 , 88 , 124 126 ), while reduced glutamate release was observed in cortical and hippocampal nerve endings of both mice and rats suffering from EAE disease ( 72 , 88 , 100 , 126 , 127 ). As to glutamate receptors, both metabotropic and ionotropic glutamate receptors (namely mGlu1/5 and mGlu4, mGlu2/3 receptors, and NMDA and AMPA receptors) control glutamate release ( 83 , 109 , 113 , 115 , 116 , 128 , 129 ).…”
Section: Glutamate In Demyelinating Disordersmentioning
confidence: 99%
“…The existence of CCR1, CCR3, and CCR5 receptor proteins in neurons was then confirmed by other groups ( 20 , 78 81 ), despite some discrepancies concerning their exact location (in the soma, on axonal processes and/or in nerve terminals). As to this aspect, a relevant finding was that CCR1, CCR3, and CCR5 receptor proteins exist in both human and rodent cortical nerve endings, as well as in rodent spinal cord terminals, i.e., in those parts of neuron where transmitter exocytosis occurs ( 66 , 71 , 72 ).…”
Section: Ccl5 In Neuronsmentioning
confidence: 99%